Applied Plasticity, Second Edition - Chakrabarty, Jagabandhu; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Applied Plasticity, Second Edition, covers advanced topics in plasticity comprehensively and in detail. This new edition has been updated throughout and includes a large set of homework problems for each chapter, making it ideal for classroom use. All relevant topics are covered, including the mathematical theory of plasticity, the theory of plane plastic stress, the axially symmetrical plastic state, the plastic behavior of plates and shells, the plasticity of metal forming processes, the theory of buckling in the plastic range, topics in dynamic plasticity, and the finite element method. Features of the new edition include: A full chapter on the Finite Element Method, previously published as an appendix; A new section on yield line theory for plate bending, including the estimation of upper bounds on the limit load; Updated chapters throughout to reflect recent advances and new developments in the field; Homework problems for chapters one through eight; A solutions manual available to professors; Fully updated references. Applied Plasticity, Second Edition, is appropriate for use by graduate students studying mechanical, civil, and structural engineering, as well as applied mechanics, and will also serve as a useful reference for engineers working in these fields.
Fundamental Principles -- Problems in Plane Stress -- Axisymmetric and Related Problems -- Plastic Bending of Plates -- Plastic Analysis of Shells -- Plastic Anisotropy -- Plastic Buckling -- Dynamic Plasticity -- The Finite Element Method.
Keywords: Engineering; Mechanics, applied; Materials; Mechanical engineering; Engineering; Continuum Mechanics and Mechanics of Materials; Theoretical and Applied Mechanics; Mechanical Engineering